Relationship between adult subventricular neurogenesis and Alzheimer’s disease: Pathologic roles and therapeutic implications - Kim, Hyeon Soo; Shin, Seong Min; Kim, Sujin; Nam, Yunkwon; Yoo, Anji; Moon, Minho (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is a neurodegenerative disease that is characterized by irreversible cognitive decline. Senile plaques formed by amyloid-β (Aβ) peptides and neurofibrillary tangles, consisting of hyperphosphorylated tau protein accumulation, are prominent neuropathological features of AD. Impairment of adult neurogenesis is also a well-known pathology in AD. Adult neurogenesis is the process by which neurons are generated from adult neural stem cells. It is closely related to various functions, including cognition, as it occurs throughout life for continuous repair and development of specific neural pathways. Notably, subventricular zone (SVZ) neurogenesis, which occurs in the lateral ventricles, transports neurons to several brain regions such as the olfactory bulb, cerebral cortex, striatum, and hippocampus. These migrating neurons can affect cognitive function and behavior in different neurodegenerative diseases. Despite several studies indicating the importance of adult SVZ neurogenesis in neurodegenerative disorders, the pathological alterations and therapeutic implications of impaired adult neurogenesis in the SVZ in AD have not yet been fully explained. In this review, we summarize recent progress in understanding the alterations in adult SVZ neurogenesis in AD animal models and patients. Moreover, we discuss the potential therapeutic approaches for restoring impaired adult SVZ neurogenesis. Our goal is to impart to readers the importance of adult SVZ neurogenesis in AD and to provide new insights through the discussion of possible therapeutic approaches.